2017
DOI: 10.1088/1742-5468/aa75e1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of side motion in the dynamics of interacting molecular motors

Abstract: To mimic the collective motion of interacting molecular motors, we propose and discuss an open two-lane symmetrically coupled interactive TASEP model that incorporates interaction in the thermodynamically consistent fashion. We study the effect of both repulsive and attractive interaction on the system’s dynamical properties using various cluster mean field analysis and extensive Monte Carlo simulations. The interactions bring correlations into the system, which were found to be reduced due to the side motion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…For complex dynamic processes that involve correlations simple mean-field methods, which assume that the occupation of neighboring sites are independent from each other, fail to properly describe the systems properties. In this case, more advanced cluster mean-field methods are required [39]. The main idea here is to consider dynamics inside of a cluster of several sites exactly, while the correlations between the clusters can be neglected.…”
Section: Cluster Mean-field Theorymentioning
confidence: 99%
“…For complex dynamic processes that involve correlations simple mean-field methods, which assume that the occupation of neighboring sites are independent from each other, fail to properly describe the systems properties. In this case, more advanced cluster mean-field methods are required [39]. The main idea here is to consider dynamics inside of a cluster of several sites exactly, while the correlations between the clusters can be neglected.…”
Section: Cluster Mean-field Theorymentioning
confidence: 99%
“…Besides LK, the presence of mutual interactions among particles also has a major impact on the steady-state properties of DDS. The driven exclusion processes with nearestneighbor interactions and without LK have been extensively studied for a single [1,16,[19][20][21][22][23][24][25][26][27][28][29] as well as multilane TASEP systems [30,31], using the thermodynamically consistent [27][28][29][30][31] and phenomenological approaches [1,16,[19][20][21][22][23][24][25]. The interactions in these systems are theoretically handled using the cluster mean-field and the modified cluster mean-field approaches.…”
Section: Introductionmentioning
confidence: 99%
“…1. This picture is inspired by the transport of kinesins along microtubule cytoskeleton filaments [21][22][23]. Each lattice site can be occupied or empty, and no more than one particle can be found at the same location -this is the exclusion part of the interactions.…”
Section: Modelmentioning
confidence: 99%
“…At the same time, the single-molecule imaging of in vitro dynamics and processivity of kinesin molecules concluded that kinesins most probably weakly repel during each encounter [13]. The importance of interactions for motor proteins stimulated multiple theoretical investigations that aimed to uncover the role of interactions in the collective dynamics [14][15][16][17][18][19][20][21][22][23]. Most of them utilized totally asymmetric simple exclusion processes (TASEPs), which are non-equilibrium multi-particle models that have been widely employed to analyze various dynamic processes in chemistry, physics and biology [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation